2009
DOI: 10.1152/physiolgenomics.90358.2008
|View full text |Cite
|
Sign up to set email alerts
|

Isolation stress for 30 days alters hepatic gene expression profiles, especially with reference to lipid metabolism in mice

Abstract: . Isolation stress for 30 days alters hepatic gene expression profiles, especially with reference to lipid metabolism in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…Therefore, we were unable to keep male littermates of some of the wild-derived strains in the same cage. It has been reported that housing the mice for long periods in isolation tends to induce excessive stress that may interfere with our observations (Motoyama et al, 2009). Furthermore, we surmised that the social interaction would tend to synchronize all the individuals in a group, potentially making our subsequent form estimates of daily activity across subjects within a co-housed group more coherent (e.g.…”
Section: Materials and Methods Micementioning
confidence: 64%
“…Therefore, we were unable to keep male littermates of some of the wild-derived strains in the same cage. It has been reported that housing the mice for long periods in isolation tends to induce excessive stress that may interfere with our observations (Motoyama et al, 2009). Furthermore, we surmised that the social interaction would tend to synchronize all the individuals in a group, potentially making our subsequent form estimates of daily activity across subjects within a co-housed group more coherent (e.g.…”
Section: Materials and Methods Micementioning
confidence: 64%
“…We also have analyzed the hepatic gene expression profiles of the mice exposed to social isolation stress for 4 weeks using DNA microarrays. The lipid metabolism-related pathway through the peroxisome proliferator-activated receptor alpha subtype was remarkably down-regulated, and the lipid biosynthesis pathway controlled by sterol regulatory element binding factor 1 was significantly up-regulated without changing body weight compared with the control (Motoyama et al, 2009). Above all, these results led us to hypothesize that prolonged social isolation stress for more than 4 weeks would activate lipid biosynthesis and enhance energy accumulation, particularly in the liver, and result in excess weight gain and hepatic hypertrophy.…”
Section: Introductionmentioning
confidence: 93%
“…We recently investigated the biological responses of mice exposed to social stress comprising isolation with a reduced volume of bedding (2 g/cage) (Miyashita et al, 2006;Nishio et al, 2007;Motoyama et al, 2009). In our system, the control group was the grouped-housing (5 mice/cage) with a standard volume of bedding (40 g/cage).…”
Section: Introductionmentioning
confidence: 99%
“…1 Stress modulates gene expression, behavior, metabolism and immune function. 2, 3, 4, 5 Chronic stress has been shown to impair lymphocyte proliferation, vaccination efficacy, 6, 7, 8, 9 wound healing 10, 11 and natural killer (NK) cell activity, and to increase the risk for bacterial and viral infection 12 and cancer. 13 Comprehensive descriptions of stress-affected molecular networks and pathways are needed to reveal strategies to reduce and prevent the pathophysiologic effects of prolonged intense stress.…”
Section: Introductionmentioning
confidence: 99%